1994
DOI: 10.1002/nbm.1940070308
|View full text |Cite
|
Sign up to set email alerts
|

1H MRS of high grade astrocytomas: Mobile lipid accumulation in necrotic tissue

Abstract: Sixty-four samples from six grade 4 astrocytomas were investigated ex vivo by 1H MRS at 360 MHz and subsequently by histopathology to obtain percentages of viable and necrotic tumour and grey and white matter. MR-visible lipids were detected in 87% of tumour samples. Necrotic foci were < 3 x 3 x 6 mm3. The means of the intensities/unit weight tissue of the lipid resonances at 5.33, 2.80, 1.29 and 0.89 ppm were significantly higher (p < 0.05) for three sets of comparisons: samples with 85-100% vs 50-75%; with 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
138
0
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(148 citation statements)
references
References 18 publications
9
138
0
1
Order By: Relevance
“…Consequently, events other than apoptosis or necrosis may also be responsible for the lipid resonances at 0.7 -1.5 ppm. This is in accordance with previous reports demonstrating the presence of MLs in viable tumour areas (Kuesel et al, 1994;. Recently, we performed 1 H spectroscopic investigations of a panel of human neuroblastoma cell lines in culture and found prominent ML signals in viable cells (Lindskog et al, unpublished observation).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consequently, events other than apoptosis or necrosis may also be responsible for the lipid resonances at 0.7 -1.5 ppm. This is in accordance with previous reports demonstrating the presence of MLs in viable tumour areas (Kuesel et al, 1994;. Recently, we performed 1 H spectroscopic investigations of a panel of human neuroblastoma cell lines in culture and found prominent ML signals in viable cells (Lindskog et al, unpublished observation).…”
Section: Discussionsupporting
confidence: 93%
“…These signals principally correspond to fatty acyl chains with methylene (CH 2 ) and methyl (CH 3 ) groups, and are commonly designated mobile lipids (MLs). Several reports indicate a possible correlation between the amount of MLs and tumour cell death (Kuesel et al, 1994(Kuesel et al, , 1996. Choline-(Cho) containing compounds (chemical shift ¼ 3.2 ppm) are abundant during the synthesis and degradation of cellular membranes.…”
mentioning
confidence: 99%
“…In 1993, Callies et al (1993) demonstrated a correlation between the appearance of mobile lipids in proton magnetic resonance (MR) spectra of myeloma cells, and the formation of cytoplasmic droplets (1 mm in diameter). A relation between the amount of mobile lipids and the percentage of necrosis was also evidenced in proton spectra of human brain tumour biopsies (Kuesel et al, 1994b). All these results encouraged Rémy et al (1997) to make a new estimate of the size of the compartment in which mobile lipids were confined.…”
mentioning
confidence: 76%
“…It has been suggested that the presence of lipid droplets in viable cells surrounding necrosis could be related to hypoxia Kuesel et al, 1994b). The aim of this study was to determine whether these cells were indeed hypoxic and if lipid droplets could be considered as a surrogate marker of hypoxia.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation